An Empirical Index for Labor Market Density - Gautier, Pieter A.; Teulings, Coen N. (The Review of Economics and Statistics, 2003)
We derive a structural index for labor market density based on the Ellison-Glaeser index for industry concentration. The labor market density index serves as a proxy for the number of workers that are potentially available for jobs in a particular area. The index is based on observed home-work location patterns. It is particularly useful for testing theories where the scale of the market matters. We apply this index to a standard wage equation and find that it explains almost half of the cross-region wage variance.